PENGARUH UKURAN PERUSAHAAN, OPINI AUDIT DAN PERGANTIAN AUDITOR TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Witantri Witantri; Median Wilestari (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
The study aims to examine the effect of Company Size, Audit Opinion, and Auditor Turnover on the timeliness of financial reporting. The population in this study is the consumer cylclicals sector companies listed on the Indonesia Stock Exchange for the period 2020-2022. The sampling method used was a purposive sampling method in order to obtain 87 companies. The total data processed in this study were 261 data. The type of data used is secondary data in the form of annual financial reports for companies in the consumer cyclicals sector listed on the Indonesia Stock Exchange for the period 2020-2022. The data analysis method used in this study is logistic regression with the help of SPSS software version 24. The results of the study prove that all variables of Company Size, Audit Opinion, and Auditor Turnover together positively influence the timeliness of financial reporting. Then the result of the study partially proves that Company Size has no significant effect on the timeliness of financial reporting, then Audit opinion and Auditor Turnover has a significant positive effect on the timeliness of financial reporting.